Acceptance of Islamic financial technology (FinTech) banking services by Malaysian users: An extension of technology acceptance model Available - Imran Mehboob Shaikh; Muhammad Asif Qureshi; Kamaruzaman Noordin; Junaid Mehboob Shaikh; Arman Khan; Muhammad Saeed Shahbaz (Emerald Publishing Limited, 2020)
This paper aims to examine the determinants that influence bank users’ acceptance for Islamic financial technology (FinTech) services by extending the technology acceptance model (TAM) in the Malaysian context. The survey was conducted using convenience sampling. Moreover, 205 responses were gathered from users of the Islamic bank. On the same note, the literature on determinants of Islamic FinTech acceptance and TAM was reviewed as well in a bid to contribute to the factors that are instrumental in determining the acceptance of FinTech services. Findings of the study reveal that Islamic FinTech’s services acceptance is determined by perceived ease of use, perceived usefulness and also by another variable, which is consumer innovativeness (CI). On the contrary other factors, self-efficacy and subjective norms are found not to be influential in determining Islamic FinTech’s acceptance by Islamic banking users. TAM is extended in the context of Islamic FinTech. A new variable, namely, CI is tested using TAM. CI is yet to be tested; therefore, this paper will be a useful reference for the policymakers, academicians and future researchers.